What is the Significance of Mangrove Forests: A Note - C, Govindasamy, (Current Botany, 2012)
<div style="border-bottom: windowtext 1pt solid; border-left: medium none; padding-bottom: 1pt; padding-left: 0in; padding-right: 0in; margin-left: 34pt; border-top: medium none; margin-right: 34pt; border-right: medium none; padding-top: 0in; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Mangroves occur almost exclusively in the tropics. Mangroves are found in a relatively small area of originally 17 to 20 million hectares. Mangrove area is used to refer to large variety of coastal systems which vary in productivity and in their makeup and which have differing hydrological and ecological features, depending upon the coastal morphology. They act as “coastal stabilizers, shelter belt areas, barrier of the sea erosion and as a nutrient export zone to open ocean. With regards to animal and plant resources, there occurs a total number of 193 plant species, 397 fish species, 259 crab species 256 mollusk species and 450 insects, more than 250 species of mammals, other plants and animals species diversity world wide. With respect of global warming, mangroves play a major role in controlling the concomitant sea level rise, coastal erosion and long-term community stability and also have an excellent potential of medical values. In the monetary term, the market value assessment of mangrove areas is available for entry into a coast-benefit analysis, mangrove forest will be regarded as a high-value ecosystem such as above sources of these long-term utilization of mangrove is only possible if one takes the ecological, economic and social value of this ecosystem into consideration as most essential for the eco-balance.